Black Mesoporous TiO2 Nanoparticles for Enhancing Surface Assisted Laser Desorption and Ionization in Mass Spectrum Analysis. Issue 24 (12th November 2021) - Chang, Wenya; Ouyang, Xueliang; Zhong, Huan; Liu, Daoxue; Deng, Dawei; Xie, Zhuoying
Abstract: Surface assisted laser desorption ionization mass spectrometry (SALDI‐MS) is a powerful analytical technology for the high‐throughput detection of metabolites, drugs, and other bioactive molecules. The performance of SALDI‐MS in enhancing molecules desorption and ionization mainly depends on the surface properties of matrix utilized. Here, black titanium dioxide (B‐TiO2 ) nanoparticle is used for the first time as a novel matrix for enhancing laser desorption and ionization (LDI) and demonstrates significant advantages over white titanium dioxide (W‐TiO2 ). Further, the black mesoporous TiO2 coated Fe3 O4 magnetic nanoparticles (B‐mTiO2 MNPs) are designed and prepared, which possess a high molar absorption coefficient, strong magnetic response, higher specific surface area, and ample phosphorylation binding sites. The B‐mTiO2 MNPs exhibit a superior ionization efficiency, low background signal, and good reproducibility (RSD < 10%) in the analysis of compounds with different molecular weights and practical bio‐sample. Salt tolerance of B‐mTiO2 MNPs up to 10 mm PBS, meanwhile, B‐mTiO2 MNPs also provides excellent enrichment efficiency for phosphopeptides (the detection limit low to 5 × 10 −10 M). Abstract : This paper reports a strategy of using black mesoporous TiO2 coated Fe3 O4 magnetic nanoparticles (B‐mTiO2 MNPs) as a novel matrix of surface assisted laser desorption and ionization mass spectrometry (SALDI‐MS) to enhance the desorption and ionization performance. B‐mTiO2 MNPs, with strong optical absorption at 355 nm, high specific surface area, abundant phosphopeptides binding sites, and superparamagnetism, fundamentally improved the deficiency of TiO2 substrate in the SALDI‐MS analysis.